Republic of Slovenia : Technical Assistance Report-The 2013 Property Tax Act: Evaluation of its Design and the Employed Mass Valuation System. (IMF Staff Country Reports; Country Report, 2016)
This report provides to the Ministry of Finance a review of the current mass valuation appraisal system, and further policy directions on improved tax design for a property tax that would not invite Constitutional challenge, especially in respect of tax base definition, tax rate policy, and tax relief. These measures combined would broaden the base with less rate discrimination. The mission identified the following key structural problems as to the design of the real property tax and suggested corrective steps with the view to improving collections from property taxes across Slovenia.